Pelatihan Komunikasi Efektif, Supervisi dan Masa Kerja Perawat terhadap Perilaku Caring Perawat - Hutagalung, Rosmaniar Evalina; Bunga, Asnet Leo (Journal of Telenursing (JOTING), 2025)
This study aims to analyze the influence of practical communication training, supervision, and length of service on nurses' caring behavior in nursing care. The method used is a literature review study using the PubMed, ScienceDirect, Semantic Scholar, and Google Scholar databases for publications on "effective communication," "supervision," "length of service," and "caring" in "nurses" in the period 2018 to 2023. The results showed that there were 18 articles. A total of 9 articles discussed communication training or communication with nurses' caring behavior, while two articles discussed supervision with nurses' caring behavior. The results were five articles for the variable length of service with caring behavior. There were two articles discussing communication and supervision with nurses' caring behavior. In conclusion, there is a significant relationship or influence between effective communication and nurses' caring behavior. The same applies to the influence between length of service and nurses' caring behavior. The variable of clinical supervision with nurses' caring behavior shows that there is an influence between these variables. Keywords: Nurse Caring, Length of Service, Effective Communication Training, Supervision